vanglisation sur Internet par le Tmoignage de la foi - Dimas Danang Agus Widayanto (P3TK, Sanata Dharma University, 2020)
Since her existence, the Church has assumed her vocation to evangelize through various means of communication. Indeed, many Catholics today, including those in Indonesia, are committed to the proclamation of the Gospel on the internet. How can we effectively evangelize in the digital era? Does communication through the web allow an encounter with Jesus Christ? Delving on these questions, this paper talks about the use of social media platforms (YouTube, Facebook, Instagram, and Twitter) in Indonesia for evangelization. This study, drawing on the works of Antonio Spadaro, Renaud Laby, Guy Marchessault, Jean Ladrire and Paul Ricur, brings out the effectiveness of the reading of the testimonies of faith that encourage the Christian Internet user to read Biblical texts, so that he can experience his encounter with Jesus Christ. However, it also discovers the existence of the enclave effects on the internet that prevent the encounter with otherness to become a true encounter. Thus, this paper states that the testimonies broadcasted on the social medias favor rather evangelization ad intra than evangelization ad gentes, which limits the use of the internet to communicate our faith.DOI: doi.org/10.24071/jaot.2020.020103